Landscape character assessment for Malaysia's rural landscape: A conceptual framework - Zakariya, Khalilah; Ibrahim, Putri Haryati; Abdul Wahab, Nur Amirah (2017)
The landscape character of a rural area is the distinct and recognisable patterns that are shaped by the natural, built and cultural elements found in a particular setting. It is the combination of geology, landform, soils, vegetation, land use, field patterns and human settlements that play important roles to reflect the rural landscape character of place. The rural landscape character is part of the cultural heritage. Malaysia is currently facing the rapid growth of urbanization into the rural areas, and the transformation of rural areas into formalized settings. The rural landscape may eventually lose its unique characters. Therefore, it is essential to identify what are the attributes that make up the rural landscape and how planners and designers can assess them to understand their values. Based on literature review, this article examines the existing body of work on landscape character assessment and the rural landscape characters. The aim of this article is to propose a conceptual framework on landscape characters assessment for Malaysia’s rural landscape. The conceptual framework can be used a potential method to assess the rural landscape and how it can be conserved or improved in the future. The rural landscape character assessment can guide the planning of rural areas to maintain their harmonious relationship between culture and nature in terms of the planning, design and management.